Assessing relative cost of complications following orthotopic liver transplant. Issue 4 (14th February 2018) - Bhutiani, Neal; Jones, Christopher M.; Cannon, Robert M.; Wei, David; Goldstein, Laura; Roy, Sanjoy; Philips, Prejesh; Scoggins, Charles R.; McMasters, Kelly M.; Martin, Robert C. G.
Abstract: Introduction: Perioperative complications impose both a clinical and financial burden on patients and the healthcare system. This study sought to identify the frequency and economic impact of complications following orthotopic liver transplantation (OLT). Methods: The Premier Perspective ® Hospital Database was queried for patients undergoing OLT between 2008 and 2015. Complications were identified by ICD‐9 code and grouped by complication type. Complication frequency as well as impact on clinical and economic outcomes was calculated. Complication frequency and effect on cost were combined to determine the annual impact of each complication type on perioperative OLT cost. Results: Among 2747 OLT patients, the most common groups of complications following OLT were pulmonary, bleeding, and infectious. The complications with the greatest average effect on treatment‐related costs were infectious, neurologic, deep vein thrombosis/pulmonary embolus, and hepatic arterial thrombosis. Infectious, pulmonary, and bleeding complications had the greatest annual effect on perioperative OLT cost. Conclusions: Efforts focused on preventing coagulopathic bleeding, improving post‐operative pulmonary toilet, and minimizing sources of infection can help improve the cost‐effectiveness of OLT. Additionally, the combination of these cost data and systematized protocols can help insurers construct bundled payments for OLT that more accurately reflect the cost of perioperative transplant care.